Effect of Doses Compost and PGPR on the Growth and Yield of Pakcoy Plants (Brassica rapa L.) - Sari, Dwi Ratna; Fuskhah, Eny; Darmawati, Adriani (Universitas Muhammadiyah Malang, 2022)
Pakcoy is a viable horticultural plant. High consumer demand, but the national pakcoy production is still low. This study aimed to examine the effect of various compost doses and PGPR doses on the growth and yield of pakcoy plants. This study used a 5x4 factorial RAL with 3 replications. The first factor is compost dosage (K) consisting of K0 = 0 kgN/ha compost, K1 = 138 kgN/ha compost, K2 = 69 kgN/ha compost, and K3 = 138 kgN/ha compost, K4 = 207 kgN/ha compost. The second factor is the PGPR dose (P) consisting of P0 = 0 ml/l water, P1 = 5 ml/l water, P2 = 10 ml/l water, and P3 = 15 ml/l water. The results showed that offering compost as much as 207 kgN/ha increased the growth and yield of pakcoy plants compared to giving 138 kgN/ha of inorganic fertilizer. The increase in the PGPR dose that was applied 2 times at planting and 14 days after planting (DAT) of 200 ml did not significantly increase the growth and yield of pakcoy plants.